2003
DOI: 10.1017/s0144686x02001101
|View full text |Cite
|
Sign up to set email alerts
|

Making a move: care-home residents' experiences of relocation

Abstract: Studies in environmental gerontology have progressed our understanding of the ways in which older people respond to and manage the environments in which they live, including their decisions about relocation and the influencing factors. Much of this work, however, has been done with relatively healthy and mobile older people living in domestic environments. It is often the case that when care-home residents move, the decisions are taken by others while the residents are passive and maybe hardly consulted. Far f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
33
0
10

Year Published

2009
2009
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(47 citation statements)
references
References 17 publications
4
33
0
10
Order By: Relevance
“…Some individuals consciously aim at decreasing environmental press by changes in their physical home environment to stay as independent as possible, for as long as possible. Very old people seem to be aware of the environmental press of their home environment in relation to health, and decisions on relocation can be seen as actions to change the environment to accommodate to health changes that cannot be overcome in the present home (Chen and Wilmoth 2004;Reed et al 2003). Positive effects among older people relocating to sheltered housing have been demonstrated by others as well (Chen and Wilmoth 2004;Svidén et al 2002), while the current study adds to our knowledge of the role of home and health dynamics.…”
Section: Discussionsupporting
confidence: 63%
See 1 more Smart Citation
“…Some individuals consciously aim at decreasing environmental press by changes in their physical home environment to stay as independent as possible, for as long as possible. Very old people seem to be aware of the environmental press of their home environment in relation to health, and decisions on relocation can be seen as actions to change the environment to accommodate to health changes that cannot be overcome in the present home (Chen and Wilmoth 2004;Reed et al 2003). Positive effects among older people relocating to sheltered housing have been demonstrated by others as well (Chen and Wilmoth 2004;Svidén et al 2002), while the current study adds to our knowledge of the role of home and health dynamics.…”
Section: Discussionsupporting
confidence: 63%
“…In other words, in very old age the relationship between housing and health is significant due to the increased vulnerability to environmental challenges ). Thus, relocation can be seen as an action to change the social and physical environment, taken in order to accommodate to health changes that cannot be overcome in the present home (Chen and Wilmoth 2004;Reed et al 2003), while recent empirical evidence for such mechanisms is scarce.…”
Section: Introductionmentioning
confidence: 97%
“…Previous research has suggested that elders' ability to view relocation as voluntary, desirable, or important has been critical in the process of adjustment (Chen et al, 2007;Johnson & Hlava, 1994;Porter & Clinton, 1992;Prager, 1986;Thomas & Hayley, 1991). Therefore, interventions should be directed toward enhancing pulling factors through helping elders to become familiar with the facility by encouraging a site visit to the facility before they move, helping them to develop relationships with other residents who already live there, and helping them to evaluate the care that is available and to engage in the facility's activities to increase their feelings of security and increase their socialization (Oldman & Quilgars, 1999;Reed, Cook, & Stanley, 1999;Reed, Cook, Sullivan, & Burridge, 2003). Other interventions could include showing the elders a video that describes the facility if they cannot come to visit, individual counseling and group discussion with family members (which can be important for some residents), and helping elders to express their feelings toward the move; these would contribute to more security.…”
Section: Discussionmentioning
confidence: 98%
“…For example, studies on pressures to speed up discharge have shown that they may inadvertently lead to higher mortality risks and have exposed the lack of involvement of older people in decisions to move to residential care. [40][41][42][43] Systemic nature of abuse How can we acknowledge these views? We need to ensure that the voices of older people are heard and their experiences find resonance.…”
mentioning
confidence: 99%